Store Atmosphere terhadap Consumer Satisfaction melalui Experiential Marketing dan Perceived Quality Baso Japri Tasikmalaya - Laela, Ela; Putri, Mega Amalia; Ningrat, Sri Rahayu; Hakiki, Rudi; Awalludin, Ripal Anwar; Muiz, Aris Nurul (Sosio e-Kons, 2023)
Consumer satisfaction is a vital aspect that needs to be studied comprehensively to win market share amid the current competition. One of the Tasikmalaya culinary businesses that is currently developing and much loved by the community is Baso Japri. This study aims to identify the effect of store atmosphere through experiential marketing and perceived quality on consumer satisfaction at Baso Japri Tasikmalaya. The quantitative method with a sample of 100 respondents was taken using a non-probability sampling technique used in this study and analyzed using the partial least squares (PLS) technique with the SmartPLS 3.0 program. The data obtained were then analyzed using outer loadings, construct reliability and validity, discriminant validity, and path coefficient. The results of the study show that: 1) experiential marketing has a significant effect on consumer satisfaction of 5,601; 2) perceived quality has a significant effect on consumer satisfaction of 6,531; 3) store atmosphere has a significant effect on experiential marketing of 20,176; 4) store atmosphere has a significant effect on the perceived quality of 20,703; 5) store atmosphere has a significant effect on consumer satisfaction with experiential marketing as a mediating variable of 5,447. 6) store atmosphere has a significant effect on consumer satisfaction with perceived quality as a mediating variable of 6,032. For further consumer satisfaction research, it is hoped that researchers can increase the sample and complete the data so that there is more data and can support one another.